Paroxysmal Atrial Fibrillation Catheter Ablation Outcome Depends on Pulmonary Veins Anatomy - Odozynski,Gabriel (2018)
Abstract Background: Pulmonary veins (PV) are often the trigger to atrial fibrillation (AF). Occasionally, left PVs converge on a common trunk (LCT) providing a simpler structure for catheter ablation. Objective: To compare the clinical characteristics and outcomes of ablation in paroxysmal atrial fibrillation (PAF) of patients with or without LCT. Methods: Case-control study of patients undergoing first-ever catheter ablation procedure for drug refractory PAF. The information was taken from patients' records by means of a digital collection instrument, and indexed to an online database (Syscardio(r)). Clinical characteristics and procedures were compared between patients with or without LCT (LCT x n-LCT), adopting a level of statistical significance of 5%. The primary endpoint associated with efficacy was lack of atrial arrhythmia over the follow-up time. Results: One hundred and seventy two patients with PAF were included in the study, 30 (17%) LCT and 142 (83%) n-LCT. The clinical characteristics, comorbidities, symptoms scale and risk scores did not differ between the groups. There was AF recurrence in 27% of PAF patients in the n-LCT group and only 10% of patients in the LCT group (OR: 3.4 p: 0.04) after a follow-up of 34 ± 17 months and 26 ± 15 months respectively. Conclusion: Patients with a LCT have a significantly lower recurrence rate when compared to patients without this structure. It is mandatory to report the results of AF catheter ablation as a PV anatomical variation function.